A Neurological and Ideological Perspective of Ethical Leadership - Waldman, David A.; Wang, Danni; Hannah, Sean T.; Balthazard, Pierre A. (Academy of Management Journal, 2017)
A growing body of literature has considered the outcomes of ethical leadership in terms of positive effects on followers. However, little research has addressed its antecedents. We thus have insufficient knowledge of the personal characteristics or qualities of ethical leaders. Accordingly, the current research draws on conceptualizations of what constitutes the moral self through conceiving such characteristics largely in terms of a neurological index derived through quantitative electroencephalogram, in combination with ethical ideology. Integrating neuroscience and moral psychology, our findings suggest that the interaction of leader relativism and idealism partially mediates the effects of the brain’s default mode network in the prediction of ethical leadership.